Review of childhood pain highlights the role of negative stress. (26th June 2019) - Alfven, G; Grillner, S; Andersson, E
Abstract: Aim: Recurrent pain of unknown origin is a major problem in children. The aim of the present review was to examine the hypothesis of negative stress as an aetiology of recurrent pain from different aspects. Methods and Results: Epidemiological studies, clinical experience and hormonal data give support for such a hypothesis. Negative stress as a tentative aetiology for recurrent pain is reviewed. Stress, muscular tension, the startle reaction and its tentative relation to pain is illuminated. Deviations of hormonal secretion supporting a stress aetiology are mentioned. The role of central sensitisation for recurrent pain is discussed. Possible aetiological implications of recurrent pain as a local symptom or a general disorder are presented. Brain changes due to stress are shortly reviewed. Stress and pain in the clinic are highlighted. The importance of biological, psychological and social factors, as well as genetic elements, is discussed. Conclusion: Stress elicits neurobiological mechanisms. They may lead to many neurophysiological deviances. Increase of muscle tension and neuromuscular excitability and enhanced startle reaction may be of importance for recurring pain. The identification of stress as a primary cause of recurrent pain can have huge implications for understanding signs and treatment in clinical practice. Abstract :